Measurement uncertainty of adaptive Chirp-z transform - Mostarac, Petar; Malarić, Roman; Hegeduš, Hrvoje (Measurement : journal of the International Measurement Confederation, 2013)
•In this paper uncertainty analysis of Adaptive Chirp Transform (ACT) has been made.•In uncertainty analysis influence of all measurement chain parts are taken into consideration.•Uncertainty propagation of ACT is analyzed according to GUM. In this paper analysis of measurement uncertainty of Adaptive Chirp-z transform (ACT) algorithm for power frequency measurement is presented. ACT is a new algorithm developed for real time monitoring of power frequency. Every element (hardware and software) of measurement chain is contributing to the total measurement uncertainty. The analysis of passive voltage dividers, analog-to-digital converters, numeric algorithms and processors (word length and type of arithmetic) are also presented. Estimated values of each contributing part of measurement chain are calculated to the final expression of measurement uncertainty.